Distracted Driving Using Mobile Phone - Ali, Atheer Muhammed (Anbar Journal of Engineering Sciences, 2021)
Approximately one-quarter of all automobile collisions in the United States are thought to be caused by a distracted or inattentive driver. As more wireless communication, entertainment, and driver assistance technologies become available in vehicles, the number of distracted driving accidents is projected to rise. Driver distraction is a major concern in North America, Europe, and Japan when it comes to road safety. The importance of driver distraction as a road safety concern, on the other hand, has just lately been recognized. This study presents an overview of current studies on in-vehicle driver distraction, with an emphasis on mobile phone usage, as this technol-ogy has garnered the most attention in the literature on driver distraction. The impact of in-vehicle gadgets on driving performance is discussed in this review. The adaptive techniques driv-ers use to maintain acceptable driving performance when distracted are discussed, as well as the situations under which these adaptive tactics can fail and how driving performance is harmed when they do. Legislation prohibiting drivers from using their cellphones while driving has had minimal effect, presumably due to a lack of regulation and enforcement. As potential preventive measures to decrease accidents caused by distracted drivers, behavior modification programs, enhanced vehicle safety, and public awareness campaigns have been created.